Experimental assessment of coupling loss factors of thin rectangular plates - PANUSZKA, R.; WICIAK, J.; IWANIEC, M. (Archives of Acoustics, 2005)
Knowledge of Coupling Loss Factors (CLF’s) for energy flow evaluation in structural elements of complex mechanical systems is fundamental. Several experiments were conducted to evaluate CLFs of different perpendicular connections of rectangular plates. The method of energy storage was conducted under acoustic free-field conditions, and a large number of thin plates with different designs of junctions were examined. The tests included two types of connections: welded line junction and point junctions. In the first type of connection, the influence of the thickness ratio of plates on CLFs values was tested. In the second type of connection the influence of the point of distribution at junctions on CLFs values were tested. Other tests were done to establish the impact of junction design on CLFs. Welded line junctions have a tendency to decrease the CLFs when the ratio of thickness of plates is increased. The CLFs also increase with density of joining points. Maximal values of CLFs were observed for spot-welded junctions. Mid-values were represented by screw-bolted joints and the lowest values by riveted junctions.